1970
DOI: 10.3329/bjms.v10i2.7809
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous extrusion of migrated fish bone in the neck after 48 hours of ingestion

Abstract: Foreign body in the neck usually will present with acute symptom of odynophagia or dysphagia. Migration of these foreign bodies to the adjacent structures or to the external skin may occur as late complication especially if the initial workup missed to detect their presence. Mostly the migrated foreign bodies were the fish bone as it has sharp ends. Depending on the tract that it made, serious complications may occur. We present a case of migrating fish bone in the neck with spontaneous extrusion without any c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Jamal et al[11] reported a patient with rapid movement of fish bone from the onset of patient’s complaint until the time of spontaneous extrusion in the neck was estimated about 72 h.…”
Section: Discussionmentioning
confidence: 99%
“…Jamal et al[11] reported a patient with rapid movement of fish bone from the onset of patient’s complaint until the time of spontaneous extrusion in the neck was estimated about 72 h.…”
Section: Discussionmentioning
confidence: 99%
“…7 It also serves as a 'road map' as it provides the surgeon with accurate size, type, orientation of foreign body and its relationship to other vital structures in the neck such as hyoid bone, thyroid cartilage, cricoid bone, carotid artery and internal jugular vein. 8 This information is very crucial especially when a neck exploration is planned. CT scans however are not without their drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Accidental ingested fish bone is a quite common problem in emergency department, especially in Asian countries where people consuming delicate un-filleted fish referred to a habbit. [1][2][3] Normally, ingested fish bone may have passing by through GI tract, but less frequently it may get impacted in esophagus. And in extreme case, it may have migrating extra luminal.…”
Section: Introductionmentioning
confidence: 99%